Late Toarcian marine gastropods from the Cleveland Basin, UK: systematics, palaeobiogeography and contribution to biotic recovery from the early Toarcian extinction event - Ferrari, Silvia Mariel (2019)
As part of a study to evaluate the recovery from the early Toarcian extinction event in the Cleveland Basin, 477 new gastropod specimens were collected from mid-late Toarcian rocks of the Ravenscar section, North Yorkshire, UK. The gastropods were preserved in two modes: 1) specimens preserved with recrystallized shells, mainly in the Whitby Mudstone Formation, but also some in the Blea Wyke Sandstone Formation; 2) specimens preserved as external moulds in mineralized patches of shells in the Yellow Sandstone Member.